A Language to Specify the Interaction Considering Agents, Environment, and Organization - Zatelli, Maicon R.; Hübner, Jomi F. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Interaction is a subject widely investigated in multi-agent systems (MASs), but there are still some open issues. Beyond the interaction usual between agents, we can conceive other kinds, like the interaction between agents and environment, or between agents and organization. These other kinds allow us to consider several situations that are not limited to speech acts. For example, the interaction between agents and environment allow us to define actions and events in interaction protocols, which would not be possible to represent with just the concept of speech act. In this paper we propose a language to specify the interaction considering the environment, organization, and agents. We also present a sketch of a dynamic of execution and some examples of protocols.